2018
DOI: 10.1002/phar.2079
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year Effectiveness Study of Intravitreous Ranibizumab in Wet (Neovascular) Age‐Related Macular Degeneration: A Meta‐Analysis

Abstract: This meta-analysis suggests visual improvements at 12 months of 0.5-mg ranibizumab use in patients with wAMD. A higher gain in VA was observed when pooling results from RCTs compared to those in observational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Improvements of BCVA were associated with significant reductions of CSFT and CSV in each study arm, without differences among the treatment regimens used. These findings are consistent with a large body of evidence of the efficacy of ranibizumab in nAMD reported in the literature (Rosenfeld et al 2006;Brown et al 2009; Comparison of Age-Related Macular Degeneration Treatment Trials (CATT) Research Group 2016; Vardarinos et al 2017;Ozkaya et al 2017;Silva et al 2017;Guo et al 2018). However, to the best of our knowledge, this is the first prospective randomized trial comparing the clinical efficacy and safety of three regimens, bimonthly, T&E and PRN in treatment-na€ ıve patients with nAMD.…”
Section: Discussionsupporting
confidence: 89%
“…Improvements of BCVA were associated with significant reductions of CSFT and CSV in each study arm, without differences among the treatment regimens used. These findings are consistent with a large body of evidence of the efficacy of ranibizumab in nAMD reported in the literature (Rosenfeld et al 2006;Brown et al 2009; Comparison of Age-Related Macular Degeneration Treatment Trials (CATT) Research Group 2016; Vardarinos et al 2017;Ozkaya et al 2017;Silva et al 2017;Guo et al 2018). However, to the best of our knowledge, this is the first prospective randomized trial comparing the clinical efficacy and safety of three regimens, bimonthly, T&E and PRN in treatment-na€ ıve patients with nAMD.…”
Section: Discussionsupporting
confidence: 89%
“…(See Appendix 1D in the supplementary material.) The mean gain in VA estimated in this analysis is supported by the results from other RBZ real-world meta-analyses (Kim et al [10], Guo et al [11]) that estimated mean gains in VA at week 52 ranging between ? 4.85 to ?…”
Section: Discussionsupporting
confidence: 84%
“…AURA also showed that several factors, including age, baseline VA score, number of injections, and regular monitoring, may be predictive of treatment outcomes and may explain the differences between real-world outcomes and RCTs [9]. Since these studies were undertaken, clinical practice has evolved; recent meta-analyses of RBZ real-world studies [10,11] showed that VA outcomes at 12 months in RBZ-treated patients were improved compared with those in AURA. Despite these improvements, treatment outcomes varied between studies, and the mean VA gain was lower in observational studies than in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al reported an improvement of +4.85 letters after 1 year in 37 observational studies with ranibizumab treatment (which included fixed-dose and PRN regimens). 29 Similarly, Kim et al reported an increase of +3.5 letters at Year 1 with ranibizumab PRN regimens (N=20 247); however, this was not maintained, reducing to +1.3 letters at Year 2 and −1.9 letters by Year 3 (N=14 408 and 11 714, respectively). 30 …”
Section: Resultsmentioning
confidence: 95%
“…Guo et al reported an improvement of +4.85 letters after 1 year in 37 observational studies with ranibizumab treatment (which included fixed-dose and PRN regimens). 29 Similarly, Kim et al reported an increase of +3.5 letters at Year 1 with ranibizumab PRN regimens (N=20 247); however, this was not maintained, reducing to +1.3 letters at Year 2 and −1.9 letters by Year 3 (N=14 408 and 11 714, respectively). 30 Three articles reported outcomes for studies including >1000 patients on PRN regimens (AURA, LUMINOUS and IRIS) and, in all, improvements in VA were observed with ranibizumab PRN treatment at 1 year compared with baseline.…”
Section: Anti-vegf Treatment In Pro Re Nata (Prn; As Needed) Regimensmentioning
confidence: 95%